Transgenerational marking of marine fish larvae: stable-isotope retention, physiological effects and health issues - Williamson, D. H.; Jones, G. P.; Thorrold, S. R.; Frisch, A. J. (Journal of fish biology, 2009)
This study examined the toxicological and physiological responses of a commercially important coral‐reef grouper, Plectropomus leopardus (Serranidae), to injection of enriched stable‐isotope barium chloride (BaCl2) solution. Thirty adult P. leopardus were subject to one of two 138BaCl2 injection treatment groups (corresponding to dosage rates of 2 and 4 mg 138Ba kg−1 body mass), and a control group in which fish were injected with 0·9% sodium chloride (NaCl) solution. Fish from each group were sampled at post‐injection intervals of 48 h and 1, 3, 5 and 8 weeks, at which time blood and tissue samples were removed from each fish. Residual concentrations of Ba and 138Ba:137Ba ratios were measured in muscle, gonad, liver and bone tissues of each experimental fish. Elevated Ba concentrations were detected in all treatment fish tissue samples within 48 h post injection. Residual Ba concentrations decreased throughout the remainder of the 8 week experimental period in all tissues except bone. The BaCl2 injection had no significant effects on measured whole blood variables or on the plasma concentrations of steroid hormones. Enriched Ba stable isotopes can therefore be used at low dosages to mark larvae of commercially important marine fishes, without adverse effects on the health of the fishes or on humans who may consume them.